Racial Restrictions on Voting: Evidence from a New Pan-Anglophone Dataset, 1730-2000 - Dhammika Dharmapala (CESifo GmbH, 2024)
A substantial literature studies franchise extension, focusing primarily on class-based – rather than race-based – voting restrictions. This paper constructs and analyzes a novel dataset that codes the presence of race-based restrictions on voting in 131 jurisdictions over 1730-2000 (consisting primarily of English-speaking subnational jurisdictions with substantial power to determine their electoral law). It documents extensive variation in these restrictions over time and across jurisdictions. To explain this variation, the paper uses a framework that emphasizes the distinction between centralized imperial control versus the empowerment of local European settlers. A difference-in-difference analysis of the impact of US independence (using “Loyalist” British colonies in the Americas as a control group) suggests a substantial positive effect of US independence on the probability of a racially restrictive franchise. More generally, a stacked event study analysis implies that the independence of colonies of settlement (and, to a lesser extent, other forms of settler empowerment) had a substantial positive effect on the probability of a racially restrictive franchise. These results are robust to controlling for the existence and abolition of property qualifications for voting. They are consistent with a framework in which an imperial government is less subject to capture by local settler elites, and thus more likely to promote franchise extension than is an empowered local settler-dominated government.
Keywords: D72; 330; voting; franchise extension; race; discrimination